Sustainable business development and its challenges - Islam, Md. Mominul (2015)
This study analyses the housekeeping service performance of two Scandic hotels and perceptions of the hotel guests about the towel re-use and food waste issues, which make both environmental and business sense. The cleaning service in the hotel rooms is analyzed by the direct observation of 50 hotel rooms contributing to guests’ satisfaction. The present study has followed qualitative research approach to perceive the service gaps of the housekeeping employees and perceived gaps of the guests as to sustainability concerned with the towel re-use and food waste issues. Notably, the study presents that hotels face the challenges of offering standard and constant housekeeping service. Furthermore, factors contributing to guests’ satisfaction on the cleaning service were tested using the Wilcoxon test. In addition, guests’ perceptions regarding the cleaning service and food waste were tested. The relevant data were collected through the questionnaire survey, observation and interview methods. The complete sample data in the questionnaire consist of 132 observations, 130 were used in the analysis. The results of the study view that satisfaction of the guests on the cleaning service differed due to the service gaps of the housekeeping personnel. Additionally, perceived gaps of the guests and their demographics made a variation on their satisfaction. Besides, the study identified guests’ satisfaction as an important factor for the hotel sustainability. Moreover, towel re-use is an important issue since the guests perceive the economic aspect along with its environmental effect. Although hotels use small plates and communication message to reduce food waste, the guests wasted food due to the poor food taste. Habitual facts of the guests were also the causes of the food waste. Food waste and towel re-use are the concerns for the hotels. However, the hotel guests perceived these two issues differently. They perceived the impact of towel re-use on the environment more important than food waste. Increasing guests’ attention as to the towel re-use and food waste issues seems to be a challenge.